Transient community awared data forwarding mechanism for intermittent connected wireless network - Jian DU; Yuanyi XIA; Junfeng ZHAO; Zheng WANG; He WANG (Dianxin kexue)
In order to solve the problem of data forwarding in intermittent connected wireless network effectively,a transient community awared data forwarding mechanism for intermittent connected wireless network (ICWN) was proposed.Utilizing the semi-Markov chain model,the transfer process of nodes’s between multiple geographic locations was described and the time probability distribution of nodes’ encountering in the future was predicted,then the encountering time and locations could be obtained,which provided theoretical basis for the selection of next relay node.Experiment results show that the proposed mechanism can effectively improve the forecasting accuracy of nodes’ encounter and has a great improvement in the data delivery ratio and transmission delay.